Hypothalamic Leptin and Ghrelin Signaling as Targets for Improvement in Metabolic Control - M. Frago, Laura; A. Chowen, Julie (Current Pharmaceutical Design, 2015)
Metabolic homeostasis requires a tight balance between energy intake and energy expenditure; hence, the physiological circuits implicated in the regulation of energy metabolism must be able to quickly adjust to changes in either side of the equation. Circulating orexigenic and anorexigenic factors, including ghrelin and leptin, are produced in the gastrointestinal tract and adipose tissue, respectively, in relation to an individual’s nutritional status. These signals interact with central metabolic circuits to regulate the production and secretion of neuropeptides implicated in the control of appetite and energy expenditure. However, this physiological equilibrium can be perturbed by diverse processes, with weight gain occurring due to a positive energy balance and weight loss taking place if there is a negative energy balance. If a situation of positive energy balance continues for an extended period of time, excess weight is accumulated and this can eventually result in obesity. Obesity has become one of the most important health problems facing the industrialized world, indicating that metabolic equilibrium is frequently disrupted. Understanding how and why this occurs will allow new therapeutical targets to be identified.
Keywords: hypothalamus